Evidence of the Palaeolithic: a digital reconstruction, prior to the landfill, of Rookery Farm, Lower Kingswood, UK - Scott-Jackson, J; Scott-Jackson, W (PADMAC Unit, 2014)
In all good detective stories there are several facets to the plot. Identifying the facts that matter and those which are no more than a distraction, is vital to solving the mystery. A classic example of an abstruse situation and the approach taken to determine both the location of a previously reported Palaeolithic knapping-site (now seemingly destroyed and buried beneath rubbish in a landfill site) along with the integrity of the recently identified Palaeolithic surface-scatters/sites on the high-level plateau at Rookery Farm, Lower Kingswood, Surrey, are addressed in this geoarchaeological research report. Surface-scatter/site investigations are generally considered ‘difficult’ in the sense of understanding site-formation and ascertaining archaeological integrity. As surface-scatters (particularly those on high-level plateaus and hilltops) may be the only evidence of a Palaeolithic presence in a region/country and could be indicative of embedded (i.e. in situ) site/s at that specific locale. This is an important challenge to be addressed. In 1999, the PADMAC Unit was set up (at the University of Oxford) with the first guide to investigating and excavating high-level Palaeolithic surface-scatters/sites published in 2000 (Scott-Jackson, 2000). The prescribed techniques use methods and concepts of the earth sciences that have, by definition, been extended to the study and interpretation of sediments and landscapes. The Unit continues to develop the modelling framework which includes geophysical techniques, geospatial 3D modelling, spatial analysis, soil/sediment analysis and artefact techno-typological analysis and to expand the range of techniques and methodologies for the investigation and excavation of Palaeolithic surface-scatters/sites in various environments (Scott-Jackson, 2011). This range of techniques and methodologies have now been widely deployed both in the UK and the Middle East (see http://users.ox.ac.uk/~padmac) in areas of Palaeolithic research as diverse as: resolving competing ‘Out of Africa’ models; early hominin use of the landscape; landscape exploitation; migration patterns and population change; lithic procurement; stone-tool manufacture (techno-typological analysis); usage of stone-tools and inter-regional (and arguably inter-species) comparative analysis of these various factors. It is anticipated therefore, that this research report will serve as a useful addition to the Palaeolithic archaeological record of Rookery Farm, Lower Kingswood.